The Patients’ Rights Charter and patient centered care in a South African hospital - Nku, Ipeleng Patience (University of the Witwatersrand, Johannesburg, 2021)
South Africa’s historical context has resulted in significant disparities and challenges in its healthcare sector. The national Patients’ Rights Charter was developed to counter these challenges by empowering patients and protecting their rights. Nevertheless, majority of patients attending hospitals remain unaware of their rights, and as a result face many frustrations associated with the quality of healthcare they receive. This research seeks to assess patients’ perceptions on the Patients’ Rights Charter and the influence that it has on the concept of patient centered care in a public South African hospital. Making use of three components of the Patients’ Rights Charter, namely confidentiality, informed consent and patient participation in decision making, the extent to which the rights are perceived by patients will be explored. The goal of this study is to assist hospitals in and around South Africa to improve patient centered care through use of the Patients’ Rights Charter. The study employed a quantitative research approach making use of fully structured questionnaires. With 200 participants observed from the medical and surgical out patients departments of the Tembisa Provincial Tertiary hospital, results revealed that 86% were aware that they have rights as patients, while only 31% were aware of existence of the Patients’ Rights Charter. Overall the research found that patient perceptions of the Patients’ Rights Charter were favourable. Correlation analysis revealed that all three constituents had a positive relationship with patient centered care, while multiple linear regression analysis found that only patient participation and informed consent directly influenced patient centered care. Thus laying focus on improving implementation of the Patients’ Rights Charter can aid hospital management in enhancing patient centered care. Such improvement in implementation would best be achieved through collaborative efforts of different systems and areas of the hospital
A research report presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, Johannesburg 2021
Keywords: Patients’ Rights Charter; Patient centered care; Confidentiality; Informed consent; Participation in decision making; UCTD; SDG-3: Good health and well-being